Pengaruh Adopsi Teknologi Digital terhadap Transformasi Digital UMKM dengan Kemampuan Berinovasi sebagai Variabel Mediasi pada Sektor Kuliner di DKI Jakarta - Nabila Az - Zahra Putri; Fitra Dila Lestari; Suparno Suparno (INDO PUBLISHING, 2026)
This study aims to analyze the effect of digital technology adoption on the digital transformation with innovation capability as a mediating variable of culinary-sector MSMEs in DKI Jakarta. The study is motivated by the still low and uneven utilization of digital technology among culinary MSMEs, most of which remain focused on transactional aspects. The research employed a quantitative approach with a survey method involving 225 culinary MSME actors in DKI Jakarta who had adopted at least one digital technology, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with SmartPLS 4. The results show that digital technology adoption has a positive and significant effect on innovation capability, innovation capability has a positive and significant effect on digital transformation, and innovation capability is proven to partially mediate the effect of digital technology adoption on digital transformation. In addition, digital technology adoption also has a direct positive and significant effect on digital transformation (β = 0.368; p < 0.001). These findings reinforce the Technology Acceptance Model (TAM) and Dynamic Capability Theory, and indicate that improving MSME digital transformation depends not only on digital technology adoption but also on business actors' ability to develop product, process, and market innovation. Therefore, strengthening innovation capability needs to be a primary focus in efforts to optimally and sustainably drive the digital transformation of culinary-sector MSMEs.